Targeting Histone Deacetylases with Natural and Synthetic Agents: An Emerging Anticancer Strategy - Singh, Amit Kumar (Nutrients, 2018)
Cancer initiation and progression are the result of genetic and/or epigenetic alterations. Acetylation-mediated histone/non-histone protein modification plays an important role in the epigenetic regulation of gene expression. Histone modification is controlled by the balance between histone acetyltransferase and (HAT) and histone deacetylase (HDAC) enzymes. Imbalance between the activities of these two enzymes is associated with various forms of cancer. Histone deacetylase inhibitors (HDACi) regulate the activity of HDACs and are being used in cancer treatment either alone or in combination with other chemotherapeutic drugs/radiotherapy. The Food and Drug Administration (FDA) has already approved four compounds, namely vorinostat, romidepsin, belinostat, and panobinostat, as HDACi for the treatment of cancer. Several other HDACi of natural and synthetic origin are under clinical trial for the evaluation of efficiency and side-effects. Natural compounds of plant, fungus, and actinomycetes origin, such as phenolics, polyketides, tetrapeptide, terpenoids, alkaloids, and hydoxamic acid, have been reported to show potential HDAC-inhibitory activity. Several HDACi of natural and dietary origin are butein, protocatechuic aldehyde, kaempferol (grapes, green tea, tomatoes, potatoes, and onions), resveratrol (grapes, red wine, blueberries and peanuts), sinapinic acid (wine and vinegar), diallyl disulfide (garlic), and zerumbone (ginger). HDACi exhibit their antitumor effect by the activation of cell cycle arrest, induction of apoptosis and autophagy, angiogenesis inhibition, increased reactive oxygen species generation causing oxidative stress, and mitotic cell death in cancer cells. This review summarizes the HDACs classification, their aberrant expression in cancerous tissue, structures, sources, and the anticancer mechanisms of HDACi, as well as HDACi that are either FDA-approved or under clinical trials.